Sub-femtomole detection of 16s rRNA from Legionella pneumophila using surface plasmon resonance imaging - Foudeh, Amir M.; Daoud, Jamal T.; Faucher, Sebastien P.; Veres, Teodor; Tabrizian, Maryam (Biosensors & bioelectronics, 2014)
Legionellosis has been and continues to be a life-threatening disease worldwide, even in developed countries. Given the severity and unpredictability of Legionellosis outbreaks, developing a rapid, highly specific, and sensitive detection method is thus of great pertinence. In this paper, we demonstrate that sub-femtomole levels of 16s rRNA from pathogenic Legionella pneumophila can be timely and effectively detected using an appropriate designed capture, detector probes, and a QD SPRi signal amplification strategy. To achieve specific and sensitive detection, optimal hybridization conditions and parameters were implemented. Among these parameters, fragmentation of the 16s rRNA and further signal amplification by QDs were found to be the main parameters contributing to signal enhancement. The appropriate design of the detector probes also increased the sensitivity of the detection system, mainly due to secondary structure of 16s rRNA. The use of 16s rRNA from L. pneumophila allowed for the detection of metabolically active pathogens with high sensitivity. Detection of 16s rRNA in solutions as diluted as 1pM at 450μL (0.45femtomole) was achieved in less than 3h, making our approach suitable for the direct, timely, and effective detection of L. pneumophila within man-made water systems. [Display omitted] •Surface plasmon resonance (SPR) and Quantum dots (QD) for Legionellosis detection.•Sub-femtomole L. pneumophila 16s rRNA was detected using capture and detector probes.•Optimal 16s rRNA fragmentation and QD signal amplification parameters were achieved.•Detection of 1pM 16s rRNA (0.45femtomole) was achieved in less than 3h.